Evaluating the Effectiveness of Screened Lactic Acid Bacteria in Improving Crop Residues Silage: Fermentation Parameter, Nitrogen Fraction, and Bacterial Community - He, Liwen; Wang, Yimin; Guo, Xiang; Chen, Xiaoyang; Zhang, Qing (Frontiers in Microbiology, 2022)
Ensiling characteristics of sweet potato vine (SPV) and peanut straw (PS) as well as the effects of lactic acid bacteria (LAB) strains Lactococcus Lactis MK524164 (LL) and Lactobacillus farciminis MK524159 (LF) were investigated in the present study. Fermentation parameters, nitrogen fractions and bacterial community of SPV and PS were monitored at intervals during ensiling process. The results showed that inoculating LAB increased lactate production (2.23% vs 2.73%; 0.42% vs 1.67% DM), accelerated pH decline (5.20 vs 4.47; 6.30 vs 5.35), decreased butyrate (0.36% DM vs not detected), ammonia-N (6.41% vs 4.18% CP) or nonprotein-N (43.67% vs 35.82% CP). Meanwhile, it altered silage bacterial community, where the relative abundance of Lactobacillus was increased (6.67%-32.03% vs 45.27%-68.43%; 0.53%-10.45% vs 38.37%-68.62%) and that of undesirable bacteria such as Clostridium, Enterobacter, Methylobacterium or Sphingomonas was much decreased. It is suggested that the screened LAB strains LL and LF can effectively improve silage quality of SPV and PS silages.